Pentingnya Literasi Perilaku Pro-Environment Untuk Anak-Anak Bimbel Edukasia Grobogan Sebagai Upaya Membentuk Generasi Yang Peduli Terhadap Lingkungan - Salma Rosanti; Mahmudia Maulida Suswanti; Putri Ainun Nikmah; Nailis Sa'diyah (Fakultas Dakwah IAIN Jember, 2023)
The provision of literacy on pro-environmental urgency for children at the elementary school level aims to provide understanding and motivation for children to be able to consider properly how to protect, preserve, and manage the environment appropriately so that it can be felt for a long time. In addition, bearing in mind that pro-environmental behavior literacy is very much needed to prepare the next generation, who have broad insights, so that they can be empowered in the development and management of the nation in the future, This pro-environmental literacy activity was carried out at Education Bimbel, Padang Village, Responsibilityrjo District, and Grobogan Regency. This activity went smoothly as expected. While the method used in this literacy activity is to explain the material and discuss related pro-environmental urgency material, The result of this activity is that children begin to understand the importance of protecting, maintaining, and making good use of the environment in which they live. Keywords: Pro-Environment Behavior; Children; Environment